THERMO-TEMPORAL TREATMENT OF ALUMINIUM ALLOYS FOR INCREASE OF THEIR HERMITICITY - V. B. Deev (Литьë и металлургия)
The influence of different ways of refining of the m et processing for hermiticity of alloy AK7ch is investigated.